Feasibility of foam concrete using recycled brick and roof tile fine aggregates - Ahıskalı, Mehtiali; Assaad, Joseph; Ekşioğlu, Fikriye; Bayraktar, Oğuzhan Yavuz; Ahıskalı, Adem; Kaplan, Gökhan (Informa UK Limited, 2024)
Brick (BR) and roof tile (RT) fine aggregate fractions derived from construction and demolition wastes have a low recycling rate in new construction and building materials. This article assesses their suitability for replacing the limestone aggregate in foam concrete, which helps valorise such fractions and conserve natural limestone resources. Two concrete categories containing or not silica fume (SF) were investigated, while the BR and RT aggregate replacement rates were 10%, 20% and 40%. Tested properties include flow, density, water absorption, porosity, thermal conductivity, mechanical strengths, microscopy, drying shrinkage, resistance to freeze/thaw cycles and elevated temperature. Results showed that the concrete mechanical properties improved when the limestone aggregate was replaced by 10% BR or RT but gradually curtailed at higher addition rates. Such results concorded with the density, water absorption and porosity measurements. Foamed concrete containing BR is more resistant (compared to RT) to drying shrinkage, freeze/thaw cycle, and heat exposure, which was ascribed to the relatively lower BR porosity that improves the concrete mechanical properties and durability.